Dual-modality emergency management of a rare cause of an aorto-oesophageal fistula: a case report. Issue 3 (8th March 2021) - Vasanthan, Rishi; Tabbakh, Yasmin; Doran, Sophie; Baker, Daryll; Hague, Julian; Qureshi, Yassar; Dawas, Khaled; Mohammadi, Borzoueh
Abstract: Aorto-oesophageal fistula (AOF) is a life-threatening condition that usually presents with upper gastro-intestinal haemorrhage. This case report details the emergency presentation and management of a 51-year-old male who presented with hematemesis secondary to an impacted denture (ingested two years previously) in the oesophagus that had led to an AOF. This necessitated urgent thoracic endovascular aortic repair followed by thoracotomy, oesophagotomy, T-tube insertion and oesophagostomy. This is the first documentation in the literature of the dual-modality management for this rare cause of AOF and demonstrates the multidisciplinary approach to successful management of this complex yet rare presentation.